KNOWLEDGE AND PERCEPTION OF ECONOMICS STUDENTS ON IMPLEMENTING FINTECH IN THE DIGITAL ERA (Case Study of Islamic Economics Students at the State Islamic University of North Sumatra) - Yuannisa, Rizka Adlia; Ridwan, Muhammad; Arif, muhammad (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2023)
Rizka Adlia Yuannisa's research (2022) entitled, "Knowledge and Perceptions of Economics Students on the Implementation of Fintech in the Digital Era (Case Study of Islamic Economics Students at the State Islamic University of North Sumatra)" under the guidance of Thesis Advisor I, Mr. Dr. Muhammad Ridwan, MA and Dr. Muhammad Arif, MA as the supervisor of Thesis II Technological developments in Indonesia go hand in hand with technological developments in various fields, including in the economic field. This increasingly advanced and rapid technology can participate in developing the economy in Indonesia. Fintech as one of the results of technological developments in the digital financial transaction sector makes it easier for people to operate. Society itself has an important influence in developing the wheels of Islamic economics. Everything was started by young people who are used to running technology in their daily lives. Students as members of the Z generation or commonly referred to as the Alpha generation certainly play an active role in the progress of the current digital era, including advancing the Islamic economy in the digital era. Because researchers are interested in examining how student knowledge about fintech is developing at this time and also how their perceptions of Keywords: Fintech, Digital Economy, Technology Development *Corresponding author e-mail:kurnia@uinsby.ac.id fintech developments are in developing the Islamic economy in the digital era. This type of research is descriptive qualitative research using primary data where the data is directly from the respondent or the object being studied. This study used 11 respondents regarding their knowledge and perceptions of implementing fintech. According to the results of the research, some of the implementation of fintech have started to be used by generation Z, but only within the scope of E-money and are used only a few times, but in the use of sharia fintech, it is very rare for anyone to use or know about it. This type of research is descriptive qualitative research using primary data where the data is directly from the respondent or the object being studied. This study used 11 respondents regarding their knowledge and perceptions of implementing fintech. According to the results of the research, some of the implementation of fintech have started to be used by generation Z, but only within the scope of E-money and are used only a few times, but in the use of sharia fintech, it is very rare for anyone to use or know about it. This type of research is descriptive qualitative research using primary data where the data is directly from the respondent or the object being studied. This study used 11 respondents regarding their knowledge and perceptions of implementing fintech. According to the results of the research, some of the implementation of fintech have started to be used by generation Z, but only within the scope of E-money and are used only a few times, but in the use of sharia fintech, it is very rare for anyone to use or know about it.